A Facile Chemical‐Free and Universal Method for Transfer of Ultrathin Graphene‐Based Films. Issue 18 (8th August 2016) - Liu, Huiyuan; Xing, Zheng; Zhang, Jie; Pan, Jia‐Hong; Wang, Huanting; Zhang, Xiwang
Abstract : A facile chemical‐free transfer method achieving high‐quality ultrathin graphene oxide films (down to 4 nm) onto various substrates has been developed. Moreover, this method shows excellent universality in the transfer of other 2D nanosheet films and nanosheet/nanoparticle hybrid films.